The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0034-72992004000300011
|View full text |Cite
|
Sign up to set email alerts
|

Sensitividade e especificidade do potencial de média latência

Abstract: O Potencial Evocado Auditivo de Média Latência (PEAML) foi primeiramente descrito por Geisler, Frishkopf, Rosenblith em 1958.1 É caracterizado por uma série de ondas/respostas neuroelétricas gravadas no cérebro através de eletrodos de superfície. Atualmente, tem sido visto como um dos testes eletrofisioló-gicos mais promissores para a avaliação das disfunções e/ou alterações do Sistema Nervoso Auditivo Central. Suas ondas aparecem no intervalo entre 10 e 80 milissegundos (ms) após o início do estímulo auditivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 14 publications
1
20
1
16
Order By: Relevance
“…The variation between the criteria of interpretation of the MLR responses is one of the main difficulties for the validation of normative data and studies with higher level of evidence in the area. The presence of altered results in the absence of complaints or functional changes of hearing indicates the low sensitivity and specificity of the potential (24) and draws attention to the importance of careful interpretation, especially among individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation between the criteria of interpretation of the MLR responses is one of the main difficulties for the validation of normative data and studies with higher level of evidence in the area. The presence of altered results in the absence of complaints or functional changes of hearing indicates the low sensitivity and specificity of the potential (24) and draws attention to the importance of careful interpretation, especially among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…All eight studies followed the positioning pattern of the electrodes indicated by the 10-20 system (28) . The assembly A1/A2/C3/C4/Fpz with the active electrodes in the left (C3) and right (C4) temporaparietal junction, references in the lobes of the left (A1) and right (A2) ears and neutral in the midline polar front position (Fpz) is recommended in the literature (6,7,21,24) and was used in 88% of the analyzed studies. This arrangement allows the response record in the ipsilateral (C3A1 and C4A2) and contralateral (C3A2 and C4A1) derivations, as well as the comparison of results of different hemispheres and stimulated ears, required in neurological diagnosis protocols.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that these latencies occur between 10 and 80ms after a sound stimulus. [2][3][4][5] Myogenic contamination initially caused much debate about MLR generators, [24][25] which led to many studies until the neurogenic origin of these potentials was demonstrated. 26,28 It is currently known that myogenic responses of the scalp and neck muscles may be elicited by strong acoustic stimuli and/or by difficulties in relaxing the muscles during the test.…”
Section: Discussionmentioning
confidence: 99%
“…1 Auditory evoked potentials may be classified according to their latency; middle latency potentials or responses (MLRs) are waves obtained 10 to 80ms after a sound stimulus. [2][3][4][5] These waves are also known as auditory middle latency responses (AMLR), auditory middle responses (AMR), middle latency auditory evoked potentials (MLAEPs), and middle latency evoked responses (MLER). MLRs are characterized by a polyphasic potential of neuronal origin that occurs sequentially to the auditory brainstem response or evoked potential (ABR).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Schochat et al, (2004) 8 at the cutoff point used in their study, found sensitivity and specificity rates of approximately 70% for subjects with central auditory nervous system injury or auditory processing disorders, and that cutoff points of 30% and 40% (the ear or the electrode effect) are those that have the best balance between sensitivity and specificity 1 .…”
Section: Introductionmentioning
confidence: 98%